Impacts of extreme weather events on highly eutrophic marine ecosystem (Rogoznica Lake, Adriatic coast). (1st October 2015) - Ciglenečki, I.; Janeković, I.; Marguš, M.; Bura-Nakić, E.; Carić, M.; Ljubešić, Z.; Batistić, M.; Hrustić, E.; Dupčić, I.; Garić, R.
Abstract: Rogoznica Lake is highly eutrophic marine system located on the Eastern Adriatic coast (43°32′N, 15°58′E). Because of the relatively small size (10, 276 m 2 ) and depth (15 m) it experiences strong natural and indirect anthropogenic influences. Dynamics within the lake is characterized by the extreme and highly variable environmental conditions (seasonal variations in salinity and temperature, water stratification and mixing, redox and euxinic conditions, concentrations of nutrients) which significantly influence the biology inside the lake. Due to the high phytoplankton activity, the upper part of the water column is well oxygenated, while hypoxia/anoxia usually occurs in the bottom layers. Anoxic part of the water column is characterized with high concentrations of sulfide (up to 5 mM) and nutrients (NH4 + up to 315 μM; PO4 3− up to 53 μM; SiO4 4− up to 680 μM) indicating the pronounced remineralization of the allochthonous organic matter, produced in the surface waters. The mixolimnion varies significantly within a season feeling effects of the Adriatic atmospheric and ocean dynamics (temperature, wind, heat fluxes, rainfall) which all affect the vertical stability and possibly induce vertical mixing and/or turnover. Seasonal vertical mixing usually occurs during the autumn/winter upon the breakdown of the stratification, injecting oxygen-rich water from the surface into the deeper layers. Depending on the intensity and duration of the vertical dynamics (slower diffusion and/or faster turnover of the water layers) anoxic conditions could developed within the whole water column. Extreme weather events such as abrupt change in the air temperature accompanied with a strong wind and consequently heat flux are found to be a key triggering mechanism for the fast turnover, introducing a large amount of nutrients and sulfur species from deeper parts to the surface. Increased concentration of nutrients, especially ammonium, phosphate, and silicates persisting for several months after the mixing event, together with anoxic stress conditions, additionally influence already stressed ecosystem, hence shifting the community structure and food/web interactions in this marine system. Highlights: Rogoznica Lake, an extreme marine system on the east Adriatic coast. Extreme weather events as a key triggering mechanism for water layer mixing. Extreme and variable environmental conditions highly influence marine ecosystem. Shifts in community structure and food/web interactions as a response to anoxia. Ecosystem of marine lake as sentinel of climate change.